Accelerating the green transformation in the USA: new deal for the economic crisis. (1st January 2011) - Yang, Peter; Chen, Injazz
Although the United Nations called for a 'Global Green New Deal' and the American Recovery and Reinvestment Act (ARRA) includes green incentives, there is far from a consensus on whether the Green New Deal will be a key solution to the economic crisis. To inform the debate, we investigate the relationship between carbon consumption and three major problems facing the US economy – the financial crisis, rising energy prices, and climate change. Our analysis found that the wasteful consumption of finite fossil fuels and a lack of green competitiveness in the USA contribute to the unsustainable economic growth and the triple predicament of the existing carbon-based US economy. This study helps provide a framework for further analysis of more comprehensive green economic strategies that would allow real sustainable growth and provide viable solutions to both the climate crisis and the economic crisis.